Effect of curing temperature on properties of semi-efficient vulcanized natural rubber. (June 2016) - Zhang, Huan; Li, Ye; Shou, Jin-Quan; Zhang, Zhi-Yi; Zhao, Gui-Zhe; Liu, Ya-Qing
The effects of curing temperature from 140°C to 180°C on the network structure and properties of semi-efficient vulcanized natural rubber were studied. Morphological structure of the tensile section of vulcanizates was analyzed by scanning electron microscopy. The different networks and mechanical properties of samples before and after the hot oxygen aging were tested. Dynamic property of samples was studied by a rubber process analyzer. The results indicated that reaction temperature greatly affects the structure and properties of samples, and the best curing temperature was 150°C. The samples curing at 150°C had best comprehensive mechanical properties, better dynamic properties, and low heat buildup because of large cross-link density and good dispersibility.